Model Pembelajaran Kooperatif Dalam Pembelajaran IPS - Setiyani, Setiyani (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This research is motivated by an interest in seeing the application of cooperative learning models in social studies learning with the formulation: 1) Achievement  of the application of cooperative learning models in social studies learning ?, and 2) Factors - what factors are constraints in applying cooperative learning models to social studies learning ?. The data analyzed in the research comes from the publication of scientific works that have been studied first. Data search is done by using the keyword "key cooperative learning model in social studies learning". Based on the search results, 9 journals were found that met the research criteria. The nine journals were then analyzed and yielded conclusions. 1) The application of cooperative learning models especially in social studies learning must be accustomed to daily learning activities, 2) There needs to be an effort to increase understanding related to cooperative learning models especially for teachers in the form of seminars, comparative studies, or DIKLAT, and 3) Facilities and infrastructure to support cooperative learning especially in social studies learning need to be improved.